The development of Sn-Cu-Ni lead free composite solder influence by non-metallic reinforcement
For several decades, Sn-Pb alloys have been extensively used as soldering material in the electronic packaging industry. Even so due to the concern on the toxicity of lead in eutectic SnPb solders, researchers have been focussing on the development of new leadfree solders. The primary focus is to develop a new generation of interconnect materials that is equipped with a combination of good mechanical, electrical and thermal properties that fulfil the requirement of electronic industry. In this project, a new generation of lead-free (Sn-Cu-Ni) solder alloy was developed to form a composite solder. Five new lead-free composite solders were successfully synthesized using the powder metallurgy method, which consists of mixing, compaction, and sintering process. This research also assisted by a hybrid microwave assisted sintering process, which showed significant advantages in processing compared to conventional sintering method, such as rapid heating rate, shortened sintering time, less energy consumption and less expensive equipment. Five non-metallic reinforcements (Silicon Nitride, Titanium Oxide, Silicon Carbide, Silicon, and Activated Carbon) with various percentages (0, 0.25, 0.5, 0.75, and 1.0 wt. %) were intentionally incorporated into the solder matrix. The microstructure, electrical, thermal, physical properties, and mechanical properties of the composite solders were investigated. Addition of reinforcement particle into a Sn-Cu-Ni solder matrix has led to improvement in thermal performance and mechanical performance. The result also has shown there are no change in the melting temperature and electrical performance. The presence of reinforcement’s particles was effective in retarding the interfacial intermetallic layer formation. The shear strength of composite solder were improved with addition of reinforcement particles. All of composite solder system also showed better wettability which improvement in contact angle on Cu-substrate compare with monolithic solder. XRD result showed that there are no new reaction phases occur in the new composite system. Overall, the Sn-Cu-Ni composite solder showed an improvement compared to the monolithic solder and the Sn-Cu-Ni+AC were the most preferable composite solder. Its excellent mechanical properties make the Sn-Cu-Ni+AC composite solder an alternative and ideal choice to replace current lead free solder in the electronic industry